Nutrition in children with exocrine pancreatic insufficiency - Zheng, Yuhua; Mostamand, Shikib (Frontiers in Pediatrics, 2023)
Exocrine pancreatic insufficiency (EPI) is a condition defined as pancreatic loss of exocrine function, including decreased digestive enzymes and bicarbonate secretion, which leads to maldigestion and malabsorption of nutrients. It is a common complication in many pancreatic disorders. If left undiagnosed, EPI can cause poor digestion of food, chronic diarrhea, severe malnutrition and related complications. Nutritional status and fat-soluble vitamins should be carefully assessed and monitored in patients with EPI. Early diagnosis of EPI is clinically important for appropriate nutritional support and initiating pancreatic enzyme replacement therapy (PERT) which could significantly improve patient outcomes. The evaluation of the nutrition status and related unique management in children with EPI will be discussed in this review.